Modification of a Ventricular Assistance Device for a Hemiplegic Left Ventricular Assist Device Patient. Issue 1 (January 2019) - Muslem, Rahatullah; Yalcin, Yunus C.; Caliskan, Kadir; van der Heiden, Cees; van Rhijn, Hans; Bogers, Ad J. J. C.; Manintveld, Olivier C.
Abstract : Neurologic events occur in up to 18% of patients with continuous-flow left ventricular assist devices (LVAD) and is associated with significant morbidity and mortality. The current form of the LVAD equipment is not suited to serve patients who are impaired by a stroke. By creating an assistance device for the LVAD equipment, we have been able to greatly improve the quality of life and self-dependence of a hemiplegic LVAD patient.